Implementasi Management QOS Bandwidth Untuk CCTV Menggunakan Metode Simple Queue Pada BSI Cibitung - Lasman Effendi; Ridatu Oca Nitra; Muhammad Hilman Fakhriza (JURIKOM (Jurnal Riset Komputer), 2018)
The use of CCTV today is very important as a support for emergencies around the area of the company / building, and serves to assist officers in the building security room. In this case the function of CCTV only helps the officer to minimize the frequent crimes, not to reduce from the crime itself. CCTV itself only displays the image and save it in HDD to see the incident occurring in the hook. The more powerful the quality of CCTV itself is still many shortcomings that developed the resulting image quality, the area captured by the camera, therefore the supervisory function is still less effective and efficient for all things crime. In this research. By using remote monitoring using Pro Surveillance System application. To facilitate monitoring.